Permintaan Investor dan Karakteristik Keuangan terhadap Keputusan Pembayaran Dividen - Imelia Carolina Tedja; Tarsisius Renald Suganda; Fitri Oktariani (Jurnal Akuntansi)
Dividend payment decision is an essential policy of companies to provide investors’ expectation of investment returns. This research is aimed to prove the catering theory of dividend and financial characteristics affecting corporate decisions in dividend payments. The study was conducted on a manufacturing company published on the Indonesia Stock Exchange (IDX). Analyzing the prediction of catering theory and financial analysis of companies in making dividend payments is conducted using the logistic regression method. This research is a quantitative research and moreover manufacturing companies as research sample were used from 2014 to 2018. Financial statements were obtained from the Indonesia Stock Exchange (IDX). The result of this study indicated that investors’ demand has positive effect on dividend payment decisions. Hence, companies consider catering in dividend payment decisions. While corporate financial characteristics such as free cash flow have positive effect on dividend payment decisions, profitability has no influence on dividend payment decisions and moreover, leverage has a negative influence on dividend payment decisions.